Exploring the Root Causes of Burnout Syndrome among College Students: A Systematic Literature Review of Contributing Factors - Ahsanu Bil Husna; Asyifa Salsabila Rahmi; Nur Ilmya Nugraha Ningrum Irfandi Putri (Universitas Airlangga, 2025)
Background: Students are often faced with various pressures and challenges during their college studies. Academic pressure, heavy workloads, and demands to excel can be significant sources of stress. If not managed properly, these conditions can lead to burnout, a state of chronic physical, mental, and emotional exhaustion that results in decreased motivation and performance. Objectives: This article aims to explain the various factors that cause college students to burnout and its impact on health and academic performance. In addition, multiple strategies to overcome and prevent burnout among college students will also be discussed to improve their well-being during higher education. Methods: This study uses a narrative review method. Pubmed, Elsevier, and Google Scholar are used as databases to obtain appropriate articles. The keywords used in this study are